Epidemic of COVID-Associated Mucormycosis in India and a road ahead - S. Sharma; P. Sharma; U. K. Chandra; S. Javed; A. Nambiar; V. K. Sharma (Sri Lanka College of Internal Medicine, 2023)
COVID-associated Mucormycosis (CAM) was a peak-hour crisis in India. The situation arose from an unprecedented ICU workload of critical COVID-19 cases, insufficient resources and the impaired immune status of the patient. We recommend strong preventive measures, chemoprophylaxis and Amphotericin-B nebulisation for the effective management of CAM.